2019
DOI: 10.1371/journal.pone.0220255
|View full text |Cite
|
Sign up to set email alerts
|

Daily calving frequency and preterm calving is not associated with lunar cycle but preterm calving is associated with weather conditions in Japanese Black cows

Abstract: Several external factors including lunar cycle and weather conditions might be associated with calving conditions. Our objective here was to determine the effects of lunar cycle and weather conditions on calving frequency and the occurrence of preterm calving in Japanese Black cows. Calving records were obtained from 905 farms in Miyazaki Prefecture, Japan. Data were collected from 41,116 calvings. We conducted two studies: Study 1 investigated the effects of lunar cycle and weather conditions on daily calving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
2
Order By: Relevance
“…No obstante, para las variables tasa de preñez e incidencia de partos no hubo un efecto significativo de las fases lunares. Los resultados coinciden con investigaciones previas que señalan el efecto nulo de las fases lunares en tasa de preñez e incidencia de partos (Abecia et al, 2017;Mateos y Rodríguez-Ledesma, 2018;Sasaki et al, 2019), pero son contradictorios con los de Yonezawa et al (2016), quienes reportaron que la frecuencia de partos en vacas Holstein multíparas fue mayor en luna nueva y luna llena, en comparación con las otras dos fases. Estos investigadores atribuyeron sus resultados a que la gravedad lunar afecta la secreción de oxitocina en el animal.…”
Section: Resultados Y Discusionunclassified
See 1 more Smart Citation
“…No obstante, para las variables tasa de preñez e incidencia de partos no hubo un efecto significativo de las fases lunares. Los resultados coinciden con investigaciones previas que señalan el efecto nulo de las fases lunares en tasa de preñez e incidencia de partos (Abecia et al, 2017;Mateos y Rodríguez-Ledesma, 2018;Sasaki et al, 2019), pero son contradictorios con los de Yonezawa et al (2016), quienes reportaron que la frecuencia de partos en vacas Holstein multíparas fue mayor en luna nueva y luna llena, en comparación con las otras dos fases. Estos investigadores atribuyeron sus resultados a que la gravedad lunar afecta la secreción de oxitocina en el animal.…”
Section: Resultados Y Discusionunclassified
“…Estos investigadores atribuyeron sus resultados a que la gravedad lunar afecta la secreción de oxitocina en el animal. La razón biológica por la que no hubo significancia en la tasa de preñez e incidencia de partos aún se desconoce, y quizá pudiera estar asociada a la raza bovina, región geográfica, disminución de la fuerza de gravedad y estabilidad en el campo electromagnético de la tierra (Sasaki et al, 2019;Aguirre et al, 2021). La proporción de hembras y machos fue similar en las diferentes fases lunares, lo cual coincide con lo señalado por estudios previos (Abecia et al, 2017; Serrano-Díaz y Villa-Mesa, 2019) en los que tampoco encontraron significancia en la proporción de sexos.…”
Section: Resultados Y Discusionunclassified
“…Existing literature dealing with other animal species suggests that the variation in temperature and barometric pressure is related to the rate of birth in cows [ 24 ] but negatively associated with the occurrence of preterm calving in the same livestock species [ 23 ]. Other authors found that warm, dry, and calm conditions lead to earlier parturition dates and advanced juvenile development, whilst cold, wet, and windy weather delays birth timing and juvenile growth in bats [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Warm, dry, and calm conditions are linked to the advancement of the timing of reproduction and the date of termination of hibernation and a decrease in growth rate and semen quantity and quality variables in some animal species [ 19 , 20 , 21 ]. Similarly, significant associations between weather variables such as temperature, humidity, precipitation, or wind patterns and adverse pregnancy outcomes in humans [ 22 ] and cows [ 23 ] have been found. Moreover, changes in atmospheric pressure have been reported to influence the occurrence of the spontaneous onset of labor in term pregnancies and the birth rate [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%